Unveiling novel targets of paclitaxel resistance by single molecule long-read RNA sequencing in breast cancer - Lian, Bi (Sci Rep, 2019)
RNA sequencing has become one of the most common technology to study transcriptomes in cancer, whereas its length limits its application on alternative splicing (AS) events and novel isoforms. Firstly, we applied single molecule long-read RNA sequencing (Iso-seq) and de novo assembly with short-read RNA sequencing (RNA-seq) in both wild type (231-WT) and paclitaxel resistant type (231-PTX) of human breast cancer cell MDA-MBA-231. The two sequencing technology provide both the accurate transcript sequences and the deep transcript coverage. Then we combined shor-read and long-read RNA-seq to analyze alternative events and novel isoforms. Last but not the least, we selected BAK1 as our candidate target to verify our analysis. Our results implied that improved characterization of cancer genomic function may require the application of the single molecule long-read RNA sequencing to get the deeper and more precise view to transcriptional level. Our results imply that improved characterization of cancer genomic function may require the application of the single molecule long-read RNA sequencing to get the deeper and more precise view to transcriptional level.